The effectiveness of the Google My Business (GMB) platform in expanding marketing reach for Micro, Small and Medium Enterprises (MSMEs) in the Mataram Tangan Di Atas (TDA) Business Community - Muhammad Nur Zaini; Dwi Putra Buana Sakti; Muh Mujahid Dakwah (LPPM Sunan Doe, 2023)
This study aims to analyze the effectiveness of the Google My Business (GMB) platform in expanding marketing reach for Micro, Small and Medium Enterprises (MSMEs) in the Hands Above Business Community (TDA Mataram). This research methodology uses a qualitative approach with in-depth interviews as a data collection method. The results of the study show that MSMEs in the TDA Mataram Business Community face obstacles such as a lack of digital literacy and understanding of technology. However, the solutions found include training and further education about GMB, collaboration within the business community, and increasing digital literacy. In addition, strategies to maximize GMB features include optimizing business profiles, using interesting content, active interaction with customers, and evaluating GMB performance on a regular basis. The implication of this research is the importance of education, training and support in overcoming obstacles and maximizing the potential of the GMB platform for business growth. This research also shows that GMB is effective in expanding the marketing reach of Mataram TDA UMKM which can be seen from the growth in the number of new customers, sales, and market reach outside the region. It is hoped that this research can provide practical guidance for MSMEs and similar business communities in utilizing digital platforms to achieve broader marketing goals.